ÁJINIYAZ ShÍǴARMALARÍN OQÍTÍWDA INNOVACION TEXNOLOGIYALARDAN PAYDALANÍW - Sársenbaev, Q.J. (SCIENCE and SOCIETY, 2025)
The article presents scientific findings on the effectiveness of an innovative approach to teaching the works of the famous Karakalpak poet Ajiniyaz. Basically, the poet’s work talked about the advantages of using the «Aquarium» technology.